Caracterizaçao microestrutural de um aço SAE 4118h modificado submetido a diferentes tratamentos isotermicos - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2007)
A Modified SAE 4118H steel was submitted to different isothermal treatments, between 700 and 400ºC for each 50ºC range, in order to evaluate the decomposition of austenite under constant temperature. The austenitization was conducted under vacuum air pressure of 10-2 atm during 15 minutes. Then, each sample was transferred to an isothermal bath stabilized in the temperature of interest. The time of each treatment was varied from 15 to 28800 seconds depending on the temperature of treatment. After each time of treatment specimens were quenched in stirred brine in order to stop transformation. After standard metallographic preparation, samples were etched with color etchants. With these reagents, the different microconstituintes of Modified SAE 4118H steel obtained after each isothermal treatment had excellent contrast. The volumetric fractions of microconstituintes were determined by systematic manual point count. For heat treated samples between 700 and 550ºC, the Modified SAE 4118H steel presented microstructure consisting of ferrite and pearlite. The bainitic microstructure formation was detected in 500 and 400ºC range. The rate of transformation of Modified SAE 4118H steel was compared with the DIN 25CrMo4 steel, because of the similarity of composition. The Modified SAE 4118H steel presented pearlite transformation faster than the DIN 25CrMo4 steel and bainitic reaction at lowest temperatures. Reducing the temperature of treatment more refined microstructures was provided, which raised the hardness levels of the Modified SAE 4118H steel.
Microstructural characterization of a modified sae 4118h steel submitted to different isothermal treatments
Keywords: Aco carbono baixa- liga; tratamentos isotermicos; elementos de liga; diagrama; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA